Prayer and contemplative practices in theological education - Simmonds, Gemma (Concilium, 2024)
Karl Rahner insists that "we cannot have a truly spiritual life without a life of the mind." This suggests that theology is a necessary underpinning to the spiritual life, yet those today claiming to be "spiritual but not religious" pursue spirituality without any theological framework or context. Meanwhile in universities the mystical traditions of the Church are taught without any expectation of leading to personal commitment or practice on the part of the student. This article explores the ways in which theological education, prayer and contemplative practices both challenge and make sense of one another